Physiological ecology of forest production : principles, processes and models - Landsberg, J. J.; Sands, Peter J. (Amsterdam ; Boston : Elsevier/Academic Press, 2011)
Process-based models open the way to useful predictions of the future growth rate of forests and provide a means of assessing the probable effects of variations in climate and management on forest productivity. As such they have the potential to overcome the limitations of conventional forest growth and yield models, which are based on mensuration data and assume that climate and atmospheric CO2 concentrations will be the same in the future as they are now. This book discusses the basic physiological processes that determine the growth of plants, the way they are affected by environmental factors and how we can improve processes that are well-understood such as growth from leaf to stand level and productivity. A theme that runs through the book is integration to show a clear relationship between photosynthesis, respiration, plant nutrient requirements, transpiration, water relations and other factors affecting plant growth that are often looked at separately. This integrated approach will provide the most comprehensive source for process-based modelling, which is valuable to ecologists, plant physiologists, forest planners and environmental scientists. * Includes explanations of inherently mathematical models are aided by the use of graphs and diagrams illustrating causal interactions, and by examples implemented as Excel spread sheets * Uses process-based model as a framework for explaining the mechanisms underlying plant growth * Integrated approach provides a clear and relatively simple treatment * Includes access to electronic and printed spreadsheet examples of the variations of the ecophsyiological model.
Preface -- 1 Introduction -- 2 Weather and Energy Balance -- 3 Physiological Processes -- 4 Stand Structure and Dynamics -- 5 The Carbon Balance of Trees and Stands -- 6 Nutrient Dynamics and Tree Growth -- 7 Hydrology and Plant Water Relations -- 8 Modelling tree growth: concepts and review -- 9 The 3-PG Process-Based Model -- 10 Future developments -- Appendix 1 Determining solar direction and radiation -- Appendix 2 Some mathematical details of 3 PG -- Appendix 3 Further reading -- References.
Includes bibliographical references and index.
Keywords: Forest ecology; Trees -- Ecophysiology; NATURE -- Plants -- Trees; NATURE -- Ecosystems & Habitats -- Forests & Rainforests; Forest ecology; Trees -- Ecophysiology; Baum; Pflanzenphysiologie; Baum